PENGARUH MODAL KERJA TERHADAP PROFITABILITAS PT CAMPINA ICE CREAM INDUSTRY Tbk YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Risa Ratna Gumilang (POLITEKNIK PIKSI GANESHA, 2021)
A company need to capable in order to make a good plan about the proper amount of working capital based on what needed by the company, because the succesfull and the failure of company’s management in processing the working capital very affected toward the profitabolity of company. The purpose of this research is to find out the influence of working capital toward profitability of PT Campina Ice cream Industry Tbk,the research method that used is a secondary data analysis method with the quantitative approach.population in this research is PT Campina Ice Cream industry Tbk and the sample that used is the data of finance report for period 2016 – 2019 that consist of balance sheet report and income statement. The statistic method that used are determination coeficient, correlation coefficient, and hypothesis testing using the T test. The result of this research showed that there’s an influence that not really significant between the working capital and profitability